Civil Society and Common Good. Towards a New Articulation between Market, State and Civil Society (Cultura Económica, 2019)
This work analyzes some aspects of Pope Francis’ Encyclical Laudato Si' in relation to the commentaries of the Supreme Pontiff in the context of the Seminar Changing Relations Among Market, State and Civil Society held by the Pontifical Academy of Social Sciences and the Interdisciplinary Group of Catholic Universities Organization of Latin America and the Caribbean on Social Doctrine of the Church. The Earth, the common home of all living beings, is a common good that must be protected by the State and the market together with the civil society. The latter must have the courage to set the course for the construction of a new, more equitable, fairer and healthier socioeconomic order.
Keywords: LAUDATO SI'; CIVIL SOCIETY; COMMON GOOD; MARKET; STATE